The Transfiguration of Jesus (Mark 9:2-8): Epiphany or Apotheosis? - Burkett, Delbert (Journal of Biblical literature, 2019)
The present essay examines the Christology and genre of the transfiguration narrative within the context of Mark's Gospel (Mark 9:2-8). With respect to Christology, I argue that Jesus's transformation was not an epiphany but a preview of his apotheosis or deification. That is, this transformation reveals not a divine nature that Jesus already possessed but the divine nature that he would obtain in the future when he ascended to heaven. With respect to genre, I suggest that the transfiguration narrative is an apocalypse, a revelation of Jesus's future status in the heavenly world after his earthly life. This narrative presents Jesus as a human being who ascends to heaven to become a divine being. Thus, Mark's Jesus is not a god who becomes a man, but a man who becomes a god.